Reframing Slow Tourism in the Post-Pandemic Era: A Systematic Review and Regenerative Framework for Smart–Slow Destinations - Wulandari, Wisi; Jayanti, Lilis (Journal of Tourism Sustainability, 2025)
In the post-pandemic era, slow tourism has transitioned from a niche alternative to a key paradigm for sustainable destination regeneration. However, its rapid scholarly growth has produced conceptual fragmentation and inconsistent theoretical grounding. This study conducts a Systematic Literature Review (SLR) of 31 Scopus-indexed, open-access articles (2020–2025) following PRISMA 2020 guidelines to consolidate theoretical developments, behavioural determinants, and managerial strategies. A thematic analysis reveals a paradigmatic shift from temporal deceleration toward psychological restoration and mindful engagement. The emergence of slomads—long-stay digital nomads seeking autonomy and well-being—defines the behavioural landscape of post-pandemic travel. Evidence also demonstrates a “smart–slow nexus”, where technologies such as e-mobility, GIS-based spatial design, and AI visualization support sustainable access to peripheral regions. The analysis further exposes a governance paradox in the Cittàslow movement between authentic degrowth values and instrumental place marketing. Synthesising these insights, the paper proposes a Regenerative Slow Tourism Framework integrating technological innovation, psychological well-being, and co-created authenticity as drivers of resilient, value-oriented visitor economies. The framework advances theoretical consolidation and offers actionable guidance for policymakers and destination managers pursuing post-growth, regenerative tourism futures.